SCRIPT SKENARIO FILM YANG DIBUAT TIDAK SESUAI DENGAN NASKAH - Areta Edgina Apta Maharani; Hernawati; Sylvia Janisriwati (Perpustakaan Universitas Surabaya, 2021)
Abstract— Copyright is intellectual property in the fields of science, art, and literature which has a strategi c role in supporting nation building and advancing public welfare. Film is a part of cultural art work that is realized based on cinematographic rules is a cultural phenomenon. This means that the film is the result of a creative process of citizens that is carried out by combining the beauty, technological sophistication, and the system of values, ideas, norms, and human actions in society, nation and state. therefo re the development of science, technology, art, and literature, has been so rapid that it requires increased protection and guarantees of legal certainty for the creator, copyright holder, and owner of related rights. With the legal regulation on Copyright, it does not automatically stop any legal problems that occur as in the case between RAC and Director HB and RJP film producers who question the Scenario Script film